Your divine fingerprint : the force that makes you unstoppable : - Craft, Keith (HarperOne, 2013)
That which makes you different, makes you great. According to science, 99 percent of our DNA sequence is the same as other humans. Pastor Keith Craft believes that the 1 percent difference in each of us is a type of glory that God has given us. Within the pages of his motivational and inspirational self-help book are the tools to help you discover a unique fingerprint, your unique difference that your family needs, your marriage needs, your job needs, your faith needs--that the world needs. And when you embrace and live in that uniqueness, you celebrate the glory of God.--From publisher description.